DISPARITAS REGIONAL KOTA PEMATANGSIANTAR PROVINSI SUMATERA UTARA - Faty Rahmarisa; Bambang Kurniawan (Universitas Islam Islam Sumatera Utara, 2018)
Economic development basically aims to improve people’s welfare. Economic development cannot be separated from economic growth due to economic development and also in economic growth can facilitate a process of economic development. However, with the high growth of a country’s economy does not mean all its regions have the same growth rate due to the limitation and differences in terms of the potential of natural resources, human resources and the other factors that impact on the emergence of disparity. Disparity is a problem that until now cannot be eliminated. Pematang Siantar city has a low level of disparity in comparison with other cities located in North Sumatera. This study aims to estimate how big the regional disparity in the Pematang Siantar and to determine the effect of per capita GDP on disparities in the Pematang Siantar within the period of 2011-2015. This research uses GDP data and also population in North Sumatera in 2011-2015 obtained from Central Bureau of Statistics of North Sumatera. The method of analysis used in this study is he Williamson Index using PDRB per capita as the baseline data. Based on the results of the study, PDRB per capita Pematang Siantar has a negative effect against disparity in Pematang Siantar in terms of percentage increase per capita GRDP per capita. Pematang Siantar with an average disparity during the year 2011-2015 amounted to 0.030 with low disparity criteria during the study period 2011-2015.